COMIC STRIPS:A STUDY ON THE TEACHING OF WRITING NARRATIVE TEXTS TO INDONESIAN EFL STUDENTS - Fika Megawati; Mirjam Anugerahwati (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
Comic strips are proposed in the teaching of writing not only because of their appealing forms, but also due to their salient features as media to present content, organization and grammatical aspects of narrative texts. This study investigates the implementation of comic strips in teaching writing through a collaborative classroom action research at MAN Bangil. The procedures included planning, implementing, observing, and reflecting. The results show that teaching writing using comic strips through Process-Genre Based Approach (PGBA) could successfully improve studentsâ ability in writing. The findings also reveal that comic stripsâ effective implementation requires proper stories as well as sufficient teacherâs guidance during the writing process.